2015
DOI: 10.2217/rme.15.38
|View full text |Cite
|
Sign up to set email alerts
|

Microsphere-Based Gradient Implants for Osteochondral Regeneration: a Long-Term Study in Sheep

Abstract: Background:The microfracture technique for cartilage repair has limited ability to regenerate hyaline cartilage. Aim: The current study made a direct comparison between microfracture and an osteochondral approach with microsphere-based gradient plugs. Materials & methods: The PLGA-based scaffolds had opposing gradients of chondroitin sulfate and β-tricalcium phosphate. A 1-year repair study in sheep was conducted. Results: The repair tissues in the microfracture were mostly fibrous and had scattered fissures w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 55 publications
0
34
0
Order By: Relevance
“…The gradient capability that we have demonstrated with microsphere-based scaffolds allows for CS and TCP to be encapsulated in opposing gradients within a single biomaterial construct [8, 14]. We have a preliminary understanding of the mechanics and the raw material retention within these scaffolds over the crucial first month, from which we can infer gradients not only in initial material composition, but also in mechanics and degradation and release rate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The gradient capability that we have demonstrated with microsphere-based scaffolds allows for CS and TCP to be encapsulated in opposing gradients within a single biomaterial construct [8, 14]. We have a preliminary understanding of the mechanics and the raw material retention within these scaffolds over the crucial first month, from which we can infer gradients not only in initial material composition, but also in mechanics and degradation and release rate.…”
Section: Discussionmentioning
confidence: 99%
“…Monodisperse microspheres [10] were prepared according to our previously reported technology [8, 11-14]. Briefly, the polymer stream was broken into uniform polymer droplets by exposing the stream to acoustic excitation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The net ceramic content encapsulated in TCP/HAp 7:3 and TCP/HAp 1:1 groups was 30 wt%. Using the PLGA-protein and PLGA-TCP/HAp emulsions, microspheres with mean diameters ranging from 172–186 µm (Supplementary Figure 1), were fabricated via our previously reported technology [32, 21, 33, 22, 23, 27, 34, 24, 35, 28, 25, 26, 3638]. Briefly, using acoustic excitation produced by an ultrasonic transducer (Branson Ultrasonics, Danbury, CT), regular jet instabilities were created in the polymer stream, thereby creating uniform polymer droplets.…”
Section: Methodsmentioning
confidence: 99%
“…Our group has demonstrated that microsphere-based scaffolds can provide opposing signal gradients via spatio-temporal release of growth factors to facilitate regeneration of complex tissues such as the osteochondral interface [2126]. Furthermore, we have shown that opposing gradients of materials such as TCP and chondroitin sulfate can provide raw materials (i.e., bioactive signals and building blocks) to simultaneously guide the regional osteo- and chondrogenic differentiation of cells [27, 28]. Delivering raw materials in lieu of growth factors holds tremendous financial incentive for translation to the clinic by providing a more streamlined path for regulatory approval as well as saving on the cost of including the growth factor in the product.…”
Section: Introductionmentioning
confidence: 99%